2021
DOI: 10.1021/acs.macromol.1c01994
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of a Photosensitive Surfactant Inside Microgels

Abstract: Here, we investigate the kinetics of adsorption and desorption of a cationic photosensitive azobenzene-containing surfactant within anionic microgels in the dark and under continuous illumination with light of different wavelengths and show that microgels can serve as a selective absorber of one of the possible isomers of the photosensitive surfactant. The adsorption of the isomer is governed by entropic reasons at which micellization of the surfactant takes place within the microgel matrix composed of cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In general, for all wavelengths studied, incerasing the intensity of light leads first to an increase of the extent of the DO flow followed by a period of saturation; as illustrated for the case of irradiation with λ = 455 nm (Figure ), here starting from critical intensity ∼2 mW cm –2 , R C,max stays constant. The latter intensity is comparable to that at which the size change of the microgel is dominated by the surfactant adsorption/desorption rate, as discussed in our previous publication . We have shown that the kinetics of the response of the microgel size at low intensities is mostly governed by the photoisomerization rate of the surfactant within the interior of the particle, since the absorption of the trans -isomers by microgel is faster than the photoisomerization rate.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In general, for all wavelengths studied, incerasing the intensity of light leads first to an increase of the extent of the DO flow followed by a period of saturation; as illustrated for the case of irradiation with λ = 455 nm (Figure ), here starting from critical intensity ∼2 mW cm –2 , R C,max stays constant. The latter intensity is comparable to that at which the size change of the microgel is dominated by the surfactant adsorption/desorption rate, as discussed in our previous publication . We have shown that the kinetics of the response of the microgel size at low intensities is mostly governed by the photoisomerization rate of the surfactant within the interior of the particle, since the absorption of the trans -isomers by microgel is faster than the photoisomerization rate.…”
Section: Resultssupporting
confidence: 80%
“…In this case, the value of the concentration gradient and thus the extent of the DO flow depends on the light intensity. At larger intensities, the process is limited by absorption/desorption kinetics, while the photoisomerization is now much faster (see the inset in Figure ), and the equilibrium size of the microgels as well as the value of the gradient of cis -isomer concentration is maintained by the absorption rate of trans -isomers out of solution, which is not intensity dependent . Here, the extent of the DO flow is saturated at a maximum value, as observed from a constant cleaning radius of 55 or 65 μm for microgels with an AA content of 5 and 20 mol %, respectively.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…A surfactant containing a light-responsive azobenzene unit was utilized for controlled adsorption and desorption in hydrophilic poly(NiPAM- co -AA) microgels obtained from free radical polymerization (1–25 mol% AA) in aqueous microfluidic droplets by Sharma et al 76 Upon light irradiation, the surfactant shows reversible switching between the hydrophobic trans -conformation and the hydrophilic cis -conformation. The hydrophobic surfactant conformation allowed for diffusion of the surfactant into the microgel polymer network with formation of micelles, leading to microgel swelling.…”
Section: Polymer Network Embedded Micellesmentioning
confidence: 99%
“…The moieties that are utilized to render amphiphiles the photoresponsive nature are azobenzene [3][4][5][6], stilbene [7][8][9][10][11], dithienylethene [12][13][14] and spiropyran [15][16][17][18], to name a few [2]. Such amphiphiles have exhibited, for example, (i) smart principles for the dynamic control of surface tension of aqueous solutions [19], (ii) phenomenon of the light-driven diffusioosmosis upon which one can remove, gather or pattern a particle assembly at a solid-liquid interface [20], (iii) the photo-controlled stability and breakage of foams [21,22], (iv) new macroscopic functions such as liquid droplet transport [23] and bubble manipulation [15], (v) photoswitchable catalytic properties [24], (vi) photochemical OFF/ON cytotoxicity switching [25], etc.…”
Section: Introductionmentioning
confidence: 99%